DEVELOPMENT OF A CRICKET ENTREPRENEURSHIP PROGRAM ASSISTED BY AN E-MODULE TO IMPROVE THE ECONOMIC INDEPENDENCE OF SANTRI - Maryana, Ana; Ansori, Ansori; Noor, Agus Hasbi (Journal Of Educational Experts (JEE), 2026)
This study aims to develop and evaluate a cricket entrepreneurship program assisted by an e-module to improve the economic independence of students at Pesantren Baituzzuhri, Saguling, West Bandung Regency. The program integrates technical cricket farming skills, entrepreneurial management, digital marketing, and Islamic business ethics into a digital learning module. This research employed a Research and Development (R&D) approach consisting of needs analysis, product design, expert validation, revision, and field implementation. The effectiveness test involved 40 santri. Data were collected through pre-test and post-test instruments, observations, interviews, and questionnaires. The results show a consistent increase in students’ entrepreneurial knowledge, motivation, and economic outcomes across all stages. Average learning gains improved progressively, while students’ monthly business turnover increased significantly after program implementation. The findings indicate that the e-module-assisted cricket entrepreneurship program is effective in fostering independent economic skills among santri and can serve as a sustainable empowerment model for pesantren-based education. Keywords: entrepreneurship education, e-module, cricket farming, economic independence, pesantren